ANIMIZ ANIMATION MAKER AS TEACHING MEDIA DEVELOPMENT AT THE TENTH GRADE, WRITING A DESCRIPTIVE TEXT SMA NEGERI 1 MEDANG DERAS STUDENTS - Nurul Ihsani; Tiarnita Maria Sarjani Br. Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The purpose of this study was to develop Animiz Animation Maker as teaching media for writing descriptive text for the tenth grade students at SMA Negeri 1 Medang Deras. This study was classified as a Research and Development (R & D) study due to the result in the form of a product, which was derived from Borg and Gall (2003) theory with some modifications. The tenth grade students of SMA Negeri 1 Medang Deras were the subjects of this study. The procedures in carrying out this study included conducting a need analysis, determining the material, designing the first draft of media, revising the media, and producing the final product as an animation video. The data collection instruments were a combination of two strategies: interviews and questionnaires. The results of the interviews were examined as qualitative data, while the questionnaires were analyzed as quantitative data. These were student needs that included both target and learning needs. This study developed writing media based solely on descriptive text taught in the first semester. These media was based on Curriculum 2013.Keywords: Animiz Animation Maker, Research and Development (R&D), Writing Media, Descriptive Text.